Evaluation of Pyloroplasty repair by Single layer Simple Interrupted Extra Mucosal technique in Dogs: Humam H.Nazht1; Dhyaa Ab. Abood 2 and Omer Mohammed Sabeel 3 - Nazht, Humam H. (The Iraqi Journal of Veterinary Medicine, 2017)
In this study a pyloroplasty technique was designed by using a single layer simple interrupted extra-mucosal suture pattern on pyloric region in dogs. Nine adult dogs were used to induce longitudinal surgical incision in the pyloric region under general anesthesia using a combination of 15mg/kg B.W. ketamine hydrochloride 5% and 5 mg/kg B.W Xylazine hydrochloride 2%. The incision was closed by pyloroplasty technique (longitudinal incision for whole layers with transverse suturing) using single layer simple interrupted extra mucosal technique. The examination achieved by daily clinical observation, radiological finding, at the end of 21st day post operation, macroscopical and histopathological examination at the period 3rd, 7th, and 21st days post operation. The results showed no significant clinical changes in body temperature and physiological activity. The radiological findings showed good patency of the pyloric canal after 21st days post operation. The macroscopic finding shows heavy amount of the omentum adhered around the site of incision. The microscopic finding showed good healing process by re-epithelization of the mucosal layer associated with granulation tissue proliferation, angiogenesis, and less infiltration of mononuclear inflammatory cells. The conclusion indicated that single layer simple interrupted extra mucosal suture pattern technique can be used successfully in repair the pyloric stenosis in dog.